PERCEPÇÃO DOS USUÁRIOS QUANTO AO DESEMPENHO DE HABITAÇÕES DE INTERESSE SOCIAL EM RELAÇÃO À SEGURANÇA ESTRUTURAL - Prado, Ricardo; Santos, Débora; Mendes, Ludmilson (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Brazil presents a history of building low-quality housing, mainly in the segment of Social Housing. The Performance Standard (ABNT NBR 15575) is being considered as a technical and legal regulatory framework for the construction industry, because it defines the fulfillment of the "requirements of the users". This article proposes to identify users' perceptions regarding the performance of Social Housing units according to the structural safety requirements in PMCMV-FAR developments in Sergipe. The research method consisted of structured interviews with Social Housing users to evaluate their perception of the performance of their housing unit. Mann-Whitney homogeneity test was carried out to verify the hypothesis of homogeneity regarding the perception of structural performance between the structural masonry and the resistant masonry systems. The results showed a positive perception on the users' side regarding the safety structural system performance, especially of the structural masonry units.